A proposal for increasing the significance of smart city indicators evaluating green spaces - Hancz, Gabriella; Kosina, Gergő (International Journal of Engineering and Management Sciences, 2019)
The expected ecosystem services are provided by the urban green spaces only if it is developed according to the interdisciplinary criteria for city level green infrastructure. This paper introduces an analysis carried out on an urban site according to the two systems of criteria. The comparison of the two set of indicators allows for making conclusions and proposal for adopting green infrastructure criteria in the smart city methodology in order to ensure the proper planning of urban green spaces.